2013
DOI: 10.1093/ndt/gft001
|View full text |Cite
|
Sign up to set email alerts
|

Cholecalciferol in haemodialysis patients: a randomized, double-blind, proof-of-concept and safety study

Abstract: Cholecalciferol is effective and safe, and does not negatively affect calcium, phosphorus, PTH levels and vascular calcifications. Additional studies are needed to compare the impacts of nutritional and active vitamin D agents on vascular calcification and mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
49
0
2

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(67 citation statements)
references
References 40 publications
8
49
0
2
Order By: Relevance
“…43 Potential harms with nutritional vitamin D supplementation include hypercalcemia, hyperphosphatemia, and extraskeletal ossification. In our study, in which 80% or more were concomitantly treated with VDRAs, there were no significant changes in calcium or phosphorus, and this is consistent with all of the other RCTs in patients on hemodialysis, 19,[22][23][24][25][26][27]31,[33][34][35] including one study that administered 200,000 IU of cholecalciferol weekly for 3 weeks. 27 Raising the possibility that there may be harmful outcomes associated with excess nutritional vitamin D administration, an RCT in community dwelling elderly women treated with a one-time dose of 500,000 units of ergocalciferol or placebo found a 15% increase in falls and a 26% increase in fractures in the ergocalciferol arm at 1 year.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…43 Potential harms with nutritional vitamin D supplementation include hypercalcemia, hyperphosphatemia, and extraskeletal ossification. In our study, in which 80% or more were concomitantly treated with VDRAs, there were no significant changes in calcium or phosphorus, and this is consistent with all of the other RCTs in patients on hemodialysis, 19,[22][23][24][25][26][27]31,[33][34][35] including one study that administered 200,000 IU of cholecalciferol weekly for 3 weeks. 27 Raising the possibility that there may be harmful outcomes associated with excess nutritional vitamin D administration, an RCT in community dwelling elderly women treated with a one-time dose of 500,000 units of ergocalciferol or placebo found a 15% increase in falls and a 26% increase in fractures in the ergocalciferol arm at 1 year.…”
Section: Discussionsupporting
confidence: 88%
“…There have been ten previous RCTs with sample size $30 patients and follow-up $8 weeks that have assessed the effects of nutritional vitamin D or calcifediol supplementation in patients on dialysis on iPTH, 19,[22][23][24][25][26][27]31,[33][34][35] and all but one small study 33 is consistent with the present study in finding no effect on iPTH. An absence of effect of nutritional vitamin D on iPTH has also been found in stage IV CKD, 36,37 while at earlier stages of CKD, there appears to be a reduction in iPTH with nutritional vitamin D. The conclusion from a Cochrane evidence review, published in 2009 before many of the above-mentioned trials were completed, concluded that vitamin D is effective in suppressing iPTH, although (not obvious from the abstract) this statement pertains to VDRAs and not to nutritional vitamin D. 38 The results of observational studies lead one to believe that there is a reduction in iPTH in patients on hemodialysis with nutritional vitamin D supplementation, 6,8,18,39 although these studies used historical controls and are limited by other biases inherent with a nonrandomized design.…”
Section: Discussionsupporting
confidence: 82%
“…Our patients who were compliant with prescribed ergocalciferol did not have hypercalcemia at a disproportionate rate compared to non-compliant patients, suggesting concordance with the findings of a randomized controlled trial of cholecalciferol supplementation that 25(OH)D supplementation is safe in this population [21]. The reason for the lack of an observed calcemic effect are suggested by a study by Armas et al [22] that found that raising serum 25(OH)D to normal levels in HD patients using weekly cholecalciferol supplementation had no effect on intestinal absorption of calcium measured using a standardized labeled calcium meal.…”
Section: Discussionsupporting
confidence: 85%
“…Table 2 summarizes the studies assessing changes in serum 25OHD and PTH with vitamin D supplementation. [76][77][78][79][80][81][82][83][84][85][86][87][88][89][90][91][92] Supplementation with calcidiol in CKD stage 5D improved bone mineralization but had a limited effect on reducing serum PTH similar to non-CKD patients. 93,94 Several studies have also looked at the correlation between serum vitamin D level and BMD in CKD and non-CKD populations.…”
Section: Trabecular Bone Scorementioning
confidence: 99%